2019
DOI: 10.1038/s41538-019-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamyl leucine, a peptide in fermented foods, attenuates dysbiosis by increasing host antimicrobial peptide

Abstract: PyroGlu-Leu is present in certain food protein hydrolysates and traditional Japanese fermented foods. Our previous study demonstrated that the oral administration of pyroGlu-Leu (0.1 mg/kg body weight) attenuates dysbiosis in mice with experimental colitis. The objective of this study was to elucidate why such a low dose of pyroGlu-Leu attenuates dysbiosis in different animal models. High fat diet extensively increased the ratio of Firmicutes/Bacteroidetes in feces of rats compared to control diet. Oral admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Therefore, gut microbiota can modulate obesity. We have earlier demonstrated that the administration of 1 mg/kg body weight of pyroGlu-Leu attenuates high fat (60%) diet-induced dysbiosis in rats by increasing host antimicrobial peptide (Shirako et al, 2019). These facts suggest that administration of short-chain hydrophobic pyroglutamyl peptides present in miso could represent a potential dietary approach to curb obesity via the modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, gut microbiota can modulate obesity. We have earlier demonstrated that the administration of 1 mg/kg body weight of pyroGlu-Leu attenuates high fat (60%) diet-induced dysbiosis in rats by increasing host antimicrobial peptide (Shirako et al, 2019). These facts suggest that administration of short-chain hydrophobic pyroglutamyl peptides present in miso could represent a potential dietary approach to curb obesity via the modulation of gut microbiota.…”
Section: Discussionmentioning
confidence: 96%
“…A high fat diet has been shown to increase the abundance of Firmicutes and decrease the abundance of Bacteroidetes in gut microbiota in animal models (Zhang et al, 2012;Shirako et al, 2019). Firmicutes is known to increase host energy intake by converting indigestible substances in the gut to substances accessible to the host digestive system (Bä ckhed et al, 2005;Turnbaugh et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiyono et al identified 19 pyroglutamyl peptides in sake, and pyroGlu-Gln and pyroGlu-Leu were the major components [ 55 ]. PyroGlu-Leu has been reported to possess anti-microbial [ 56 ] and anti-inflammatory [ 57 ] activities. Tatsukami et al identified four peptides, [Leu/Ile]-[Leu/Ile]-[Leu/Ile], Phe-Pro-[Leu/Ile], [Leu/Ile]-[Leu/Ile]-[Leu/Ile]-Pro, and [Leu/Ile]-[Leu/Ile]-[Leu/Ile]-[Leu/Ile]-Pro, and predicted two compounds, the steroidal agent androsterone, identified as C 19 H 28 O, and angeloyloxylupanine or acetoxymatrine, identified as C 17 H 26 N 2 O 3 , in the fermentative process of “yamahai-ginjo-shikomi” sake [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soybeans are rich in soybean-specific proteins (glycinin and conglycinin), vitamin E, isoflavones (daidzein, daidzin, genistein, and glycitein), lipids rich in polyunsaturated fatty acids, lecithin, and saponin [ 17 , 44 , 45 ]. Miso also contains pyroglutamyl leucine [ 46 ], which is spontaneously generated from peptides with a glutaminyl residue at the amino terminal, during storage and processing [ 47 ]. Pyroglutamyl leucine was found to improve gut dysbiosis and colitis in mice [ 46 , 48 , 49 ] and, in fact, suppresses the excess proliferation of phylum Firmicutes , which is associated with obesity [ 49 ].…”
Section: Discussionmentioning
confidence: 99%